2008
DOI: 10.1103/physrevb.77.094417
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and capping effects in the magnetic and magneto-optical properties of nanoparticulate Co films

Abstract: Magnetic and magneto-optical properties of Co films are studied as a function of the morphology and the capping layer. We show that the nanoparticulate structure of the Co films has a clear influence on the magnetic and magneto-optical properties of the system. Kerr measurements combined with x-ray magnetic circular dichroism provide evidence of a strong correlation between the collective magnetic behavior of the system and the individual atomic magnetic response. The influence of the magnetic nature of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…These simulations were performed by means of the transfer-matrix formalism 52,53 where the MO constants of Co were obtained from a reference 1.2 nm thick Co film 76 grown under identical conditions as the Co/ V samples. The agreement between the simulated spectra and the experimental data was not satisfactory, even when taking into account the reduction of the magnetic moment ͑observed by XMCD͒ in the Co films, which was introduced by a proportional decrease of the MO constants.…”
Section: B Magneto-optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These simulations were performed by means of the transfer-matrix formalism 52,53 where the MO constants of Co were obtained from a reference 1.2 nm thick Co film 76 grown under identical conditions as the Co/ V samples. The agreement between the simulated spectra and the experimental data was not satisfactory, even when taking into account the reduction of the magnetic moment ͑observed by XMCD͒ in the Co films, which was introduced by a proportional decrease of the MO constants.…”
Section: B Magneto-optical Propertiesmentioning
confidence: 99%
“…In the case of Co, the MO constants extracted from the 1.2 nm Co film 76 were fixed as reference MO constants ͑Fig. 9͒, assuming a magnetic moment value of ref Co = 1.77 B /atom.…”
Section: B Magneto-optical Propertiesmentioning
confidence: 99%
“…This large contrast confirms the morphological indication that Co adhesion depends on the crystallinity of Alq 3 measured surface. 10 The average grain size in the smoother areas is 30-40 nm.…”
Section: Interface Effects On An Ultrathin Co Film In Multilayers Basmentioning
confidence: 99%
“…In particular, it has been shown that the interface region between metallic nanoparticles and the matrix has different optical properties. 29 In Fig. 3, we present the dielectric constants of the complementary system, i.e., Co:Au NPs layers.…”
Section: A Optical Propertiesmentioning
confidence: 99%